THE EFFECT OF GUIDED WRITING STRATEGY AND STUDENTSâ ACHIEVEMENT MOTIVATION ON STUDENTSâ WRITING COMPETENCY - A A, Komang, Handayani,; Dantes, N.; Ni Made, Ratminingsih, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at investigating whether the implementation of guided writing strategy and the studentsâ achievement motivation gave a significant effect to the studentsâ writing competency. This was an experimental research which applied 2 x 2 factorial design. The population was 6 classes (134 students) of grade X in SMAN 1 Sukasada in the academic year 2012/2013. The samples were 4 classes which were choosen by using Random Sampling and were divided into two groups, i.e. experimental group and control group. The research data were analyzed by using Statistical Two-Way ANOVA and Tukey Test. The result shows that, first, there was a significant difference on the studentsâ writing competency between the students who were taught by using guided writing strategy and conventional writing strategy. Second, there was a significant interactional effect on the studentsâ writing competency between the strategies applied and the studentsâ achievement motivation. Third, there was a significant difference on the studentsâ writing competency between the students who had high achievement motivation when they were taught by using guided writing strategy and conventional strategy. Fourth, there was a significant difference between the studentsâ writing competency of the students who had low achievement motivation when they were taught by using guided writing strategy and conventional strategy. Â  Â  Keywords: achievement motivation, guided writing strategy, writing competency.